Enhancing cognitive performance through thermal comfort: Insights from classroom renovation at Diponegoro University - Purwaningsih Ratna; Varina Eka Lailita Eti; Mahachandra Manik; Putri Ade Aisyah Arifna; Susanto Novie (E3S Web of Conferences, 2025)
International Undergraduate Program (IUP) of Industrial Engineering Department classrooms face challenges when the Wet-bulb Globe Temperature (WBGT) reaches 27.09°C and a temperature of 32.69°C, primarily due to the extensive use of glass. Direct sunlight through glass windows can raise indoor temperature. A renovation project was initiated to enhance overall comfort by closing the glass surface using wooden material. This research aims to assess the WBGT in the classroom before and after renovation to analyze the effect of the thermal comfort increase on cognitive performance. Post-renovation measurements revealed a reduction in WBGT to 24.58°C, accompanied by a decrease in temperature and humidity. The cognitive performance is measured using the Montreal Cognitive Assessment (MoCA). Cognitive performance, including response time, showed improvement after the renovation, with the introduction of plants further enhancing this effect. Beyond improving classroom comfort, the renovation also presents opportunities for energy savings by reducing reliance on air conditioning. This study demonstrates how renovations can contribute to sustainable building practices, offering both immediate educational benefits and reductions in energy consumption, particularly in tropical climates.